The African mine labourer : a study of six tribes employed in the mining industry - Naude, W. T. v. S.(Willem Tobias van Schalkwyk) (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Phil.) -- University of Stellenbosch, 1962.